Carta de Cruz Castro a Roberto H. Todd - Todd, Roberto H. (My University, 1921)
Felicitaciones y respaldo.
Keywords: Cruz Castro--Correspondence.; Cruz Castro--Correspondencia.; Todd, Roberto H.--Correspondence.; Todd, Roberto H.--Correspondencia.